Arctic PASSION Stakeholder Engagement Plan ... - Lenz, Josefine; Grosfeld, Lisa; Heerema, Sabrina; Sinisalo, Anna (Zenodo, 2023)
Collaborations of the Arctic PASSION consortium and different groups of rights holders and stakeholders will improve the knowledge about the changing Arctic environment and will develop more targeted and user-friendly services for managing and predicting Arctic change. Through the process of inclusive co-creation, Arctic PASSION strives to support, highlight, and increase the contribution and visibility of Indigenous and Local Knowledge and community-based monitoring within a pan-Arctic Observing System of Systems. Co-creation and inclusiveness are key principles of Arctic PASSION and are not exclusively embedded in the Pilot Services, but necessitates establishing workshops and dialogue platforms for broad engagement and interaction among rights holders, stakeholders and science partners across all Work Packages. This Arctic PASSION Stakeholder Engagement Plan identifies the different rights holder and stakeholder groups of the Arctic PASSION project and gives an overview on the different levels of ...